Challenges in Managing Charcot Arthropathy. Issue 3 (September 2021) - Hearty, Thomas
Abstract : Charcot arthropathy is a disabling disease and difficult to manage. The diagnosis can often be unclear because of limited accuracy of testing and differentiating it from infection can be a challenge. Whether to operate, the timing of the operation and the type of operation are wide ranging variables and there is no real consistent treatment recommendation based on strong evidence. This article presents case scenarios that are commonly seen in the orthopedic foot and ankle clinic to demonstrate the challenges the clinician faces in dealing with this difficult diagnosis. Level of Evidence: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence.